Fracture behaviour of engineering stone material. Issue 1 (5th November 2019) - Smolnicki, Michał; Cieciura, Mateusz; Lesiuk, Grzegorz; Correia, José; Stabla, Paweł
Abstract : Purpose: Engineered stone is a material which can be described as an artificial stone. The exemplary application area is sink production. There are very few research projects about this type of material. In fact, most of them are research conducted by the manufacturing company, which are limited to the basic properties of the material. However, knowledge about fracture mechanic of this material may be crucial in terms of usage. The paper aims to discuss this issue. Design/methodology/approach: Analysis of the inside structure was made using an optical microscope as well as SEM. In the paper, methods which can be used to obtain data about fracture behaviour of material are presented. Using eXtended Finite Element Method and experimental data from three-point bending of notched specimens stress intensity factors (SIFs) for I and II load modes were obtained. Finally, a comparison between the fracture initiation angle in the function of the ration of SIFs for I/II load modes and maximum tangential stress hypothesis prediction was presented. Findings: Analysis of the inside structure proves that this type of material has an uneven distribution of particle size. This can follow to void and micronotches formation and, later, to the failure of the material. A method of obtaining stress intensity factors for the discussed type of material and specimens can be successfully applied to other similar material, as proposed in this work. Standard crack angle propagation criteria are not sufficient for this type of material. Originality/value: There are very few research papers about this type of material. The subject of fracture mechanic is not properly discovered, despite the fact that IT is important in terms of the application area of these materials.